Burning mouth syndrome in Southwestern Saudi Arabian population - Part I: Prevalence - Khalil Assiri; Ali Azhar Dawasaz; Arwa Alshehri; Fatema Mohammad; Yagoub Alyami (Wolters Kluwer Medknow Publications, 2019)
Introduction: Burning mouth syndrome (BMS) is a chronic, spontaneous, nonremitting, painful burning sensation in the oral mucosa with no identifiable local lesion. The aim of this study was to determine the prevalence of BMS in Abha, Saudi Arabia. Materials and Methods: Patients attending for dental care completed a questionnaire before examination. A general health screen was then performed during which information about various conditions and medications was collected. Reports of burning/pain sensation were recorded using visual analog pain scale. Details of the dental examination, panoramic radiographs, and a structured interview concerning orofacial pain and discomfort were recorded. Results: Of 2264 patients screened, 159 were identified as having a potential diagnosis of BMS. The prevalence of BMS was 7.03% (primary in 2.87% and secondary in 4.15%). The highest prevalence was in patients aged >65 years. Forty-two percent of the 159 cases had primary BMS. There were more cases of type 1 diabetes in the group with secondary BMS. The tongue was the most common site of BMS (in 81.9%). The mean visual analog pain scale score was 4.3. Altered taste sensation was reported by 15.9% of patients and xerostomia by 47.6%. Patients taking antihypertensive medication were more prone to secondary BMS. The tongue, soft palate, and lower gums were significantly more likely to be affected (P ≤ 0.05). Conclusion: This is the first reported population-based prevalence data for BMS in the Saudi Arabian population and contributes to the nascent literature on the epidemiology of BMS.